Behaviour of biomass multicomponent ashes as adsorbents - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Current Science, 2016)
Physico-chemical characteristics of rice husk ash and baggase fly ash, commonly referred to as biomass ashes enable their use as adsorbents. Contrary to normal expectations, it is observed that larger particles have more number, narrower and deeper pores than smaller particles. As a consequence they have higher pore volume, total surface area and hence adsorption capacity. Also, the uptake rate of adsorption depends on the silica to carbon ratio, which is seen to be smaller for larger particles and hence they take a longer time to reach equilibrium. The extent of carbon content determines the capacity, whereas silica to carbon ratio determines the kinetics of adsorption. Removal of 2,4-dichlorophenoxyacetic acid, from aqueous solution was chosen as a representative case for study and the results obtained are compared with earlier reported results.
Keywords: Adsorption capacity; bagasse; biomass ash; rice husk; silica to carbon ratio

Elliptically birefringent chemically tuned liquid crystalline nanocellulose composites for photonic applications - Singh, Shiva; Bhardwaj, Shakshi; Verma, Chhavi; Chhajed, Monika; Balayan, Kajal; Ghosh, Kaushik; Maji, Pradip K. (Journal of Molecular Liquids, 2022)
Cellulose nanocrystals (CNCs) based photonic materials are one of the promising materials in the recent trends. The liquid crystalline behavior of the CNCs can be tailored to different advanced applications. The proposed research investigates the potential of CNCs as an optically active material. CNCs were tuned to hydroxypropyl nano cellulose (HPNC) with the degree of substitution 1.39. The prepared liquid crystalline HPNC were dispersed in various concentrations of monomethyl ether of polyethylene glycol to get waterborne materials with specific optical anisotropy. The extraction, modification, and morphology of the CNCs were investigated using NMR (Nuclear Magnetic Resonance), TEM (Transmission Electron Microscopy), XRD (X-ray Powder Diffraction), and FESEM (Field Emission Scanning Electron Microscopy) analysis. The prepared HPNC was analyzed using a hot stage POM (Polarized Optical Microscope) for optical anisotropy. The thermal stability of prepared CNCs and HPNC was also investigated. Upon optimization using rheology and POM, it was found that at the ratio of 1:1, HPNC (5 wt%) and mPEG (40 wt%) had the most distinct optical properties. The potential of the prepared materials can be further explored in sensing, smart coating, and security materials. (C) 2022 Elsevier B.V. All rights reserved.
Keywords: bagasse; Cellulose nanocrystals; Elliptical birefringence; liquid crystals; optical anisotropy

Lignocellulosic biomass analysis: acidic lignin recovery, characterisation, and depolymerisation - Singh, Sandip K.; Matsagar, Babasaheb M.; Dhepe, Paresh L. (Biomass Conversion and Biorefinery, 2024)
For the development of an effective lignocellulosic biomass conversion technology to biofuels and chemicals, the biomass composition analysis and their properties need to be characterised prior to biomass valorisation, including polysaccharide hydrolysis and lignin depolymerisation. In this work, a facile colorimetric titration method for the quantification of alpha-, beta-, and gamma-cellulose, pentosan, lignin, and silica percentages of wheat straw (WS) and two bagasse (BG I and II) samples was done. The result showed higher amounts of structural biopolymers (i.e. holocellulose and lignin (similar to 89.3%)) in BG compared to WS (81%) sample. Lignin recovery from BG (I and II) and WS samples was done by applying two-stage concentrated and dilute sulphuric acid hydrolysis, and maximum recovery (i.e. 21.5%; acid soluble +insoluble) of lignin obtained from BG II sample. Elemental and composition analysis results were represented substantial differences in lignin properties, including higher heat values (19.8 MJkg(-1)) of recovered lignin from BG II as well as high amounts of silica percentage from WS lignin. An intense Si-O-Si asymmetric stretching mode and/or C-O-C aliphatic aromatic ether (similar to 1100 cm(-1)) was characterised for lignin derived from WS. C-13 CP-MAS NMR exhibited variable intensities for dibenzodioxocin, spirodienone, and tricin moieties in recovered lignin samples. These lignin samples were processed for depolymerisation using homogeneous (1-methyl-3-(3-sulphopropyl)-imidazolium hydrogen sulphate) and heterogeneous (immobilised Bronsted acidic ionic liquid) catalysts to lower molar mass aromatic fractions and represented 89% and 92% organic solvent-soluble product yields respectively from WS-derived lignin.
Keywords: bagasse; Dibenzodioxocin; Holocellulose; Lignin depolymerisation; Spirodienone; Tricin; Wheat straw